Ethics builds reputation. (2015) - Mella, Piero; Gazzola, Patrizia
The objective of this study is to point out how behavioural ethics and reputation are linked and represent the conditions of existence for the corporate system, understood as a long-lasting organisation of individuals or institutions which produces outcomes for the external stakeholders. We think that ethics are pivotal in determining the success or failure of an organisation. They affect a company's reputation and help to define a business model that will thrive even in adversity. To show this link two theories are used: the firm interpreted as a social, or socio-technical, system, open to exchanges with the environment, and the firm as an open system, in its conditions of teleonomy, observed according to the model of the organisation as an efficient system of transformation (MOEST). Precisely because firms exist and operate within a given environment, ethics must signify organisational conduct, and the daily respect of human values allows the firm to achieve a coherent organisational reputation.